Thermal analysis of the Loss-of-Coolant Accident within the containment of the WWER-440 and WWER-IOOO nuclear reactors - Skorek, Janusz; Składzień, Jan (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents selected results of the analysis of thermal and mass flow transient processes within the containments of the WWER-440 and the WWER-1000 nuclear reactors during Loss-of-Coolant Accidents based on the mathematical model and computer code for LOCA simulation. General assumptions of the mathematical model (with lumped parameters) are briefly presented. Changes of thermal variables (temperature, pressure etc.) are governed by the fundamental thermodynamic equations. All these equations have the nonlinear, integral form. The whole area of the containment is divided into several control volumes. Control volumes are joined in a given mode (orifices, valves, siphon closures etc.) . The liquid phase (water) and the gaseous phase (air, steam and hydrogen) can appear in a control volume. Thermal equilibrium within an individual phase and a non-equilibrium state between phases is assumed. Heat accumulation in the walls and internal structures of the containment is taken into account and heat transfer between liquid and gaseous phases is also considered. The working mathematical model can be used for the analysis of different scenarios of LOCA within the containment of the PWR and BWR reactors. Later on the sample results of calculations of changes of pressure and temperature within the containment of the WWER-440 nuclear reactor and within the full containment of the WWER-1000 reactor are presented.